2013
DOI: 10.1017/cbo9781139481403
|View full text |Cite
|
Sign up to set email alerts
|

Memoranda, or, Chronicles of the Foundling Hospital

Abstract: Captain Coram's Foundling Hospital was established in 1739 for 'the maintenance and education of exposed and deserted young children'. Hogarth was a governor of the hospital - he donated several pictures, including his portrait of Coram - as was Handel, whose famous performances of his oratorio Messiah were given there from 1750 to raise funds. John Brownlow (1800–73), himself a foundling, was secretary of the hospital from 1849 until his retirement. He introduced improvements to the children's education and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[6]. Hans Sloane, one of the first governors, wrote in 1748: "I observed that in three infants bred without breasts, two generally dyed, or in that proportion, notwithstanding what I or others could do to help them" [4]. John Pugh cited Hanway [19]: "During the year 1765, in the workhouse of St. Clement Danes, one nurse, Mary Poole, had twenty three children committed to her care, and on the twenty fifth of January 1766, eighteen were dead, two had been discharged, and three only remained alive.…”
Section: Nutrition and Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…[6]. Hans Sloane, one of the first governors, wrote in 1748: "I observed that in three infants bred without breasts, two generally dyed, or in that proportion, notwithstanding what I or others could do to help them" [4]. John Pugh cited Hanway [19]: "During the year 1765, in the workhouse of St. Clement Danes, one nurse, Mary Poole, had twenty three children committed to her care, and on the twenty fifth of January 1766, eighteen were dead, two had been discharged, and three only remained alive.…”
Section: Nutrition and Nursingmentioning
confidence: 99%
“…During this period, a sense developed that more foundlings should be preserved. Focusing on administration, funding, education, or the institution's art collection, the history of the London Foundling Hospital has been described by its governor Hanway in 1759 [2] and 1767 [3]; its secretaries Brownlow in 1847 [4] and 1858 [5]; and Nichols in 1935 [6]; and by the historians McClure in 1981 [7] and Levene in 2006 [8]. Mathisen evaluated the 1761-71 infirmary books, describing medical treatment of older children [9,10].…”
mentioning
confidence: 99%
“…54 John Brownlow, the fi rst historian of the hospital writing in the mid-nineteenth century, stated that the history-painting scheme within the Court Room was a 'conjoint agreement' between the four artists. 55 Hitherto it has been presumed that the paintings were linked on a simplistic level via biblical narratives connected to children, as outlined above. Further the particular concentration by scholars on Hogarth's Moses has effectively isolated his painting from its companions.…”
Section: The Governors' Court Room History Paintingsmentioning
confidence: 99%